3‐D analysis of bacterial cell‐(iron)mineral aggregates formed during Fe(II) oxidation by the nitrate‐reducing Acidovorax sp. strain BoFeN1 using complementary microscopy tomography approaches. Issue 4 (14th May 2014) - Schmid, G.; Zeitvogel, F.; Hao, L.; Ingino, P.; Floetenmeyer, M.; Stierhof, Y.‐D.; Schroeppel, B.; Burkhardt, C. J.; Kappler, A.; Obst, M.
Abstract The formation of cell‐(iron)mineral aggregates as a consequence of bacterial iron oxidation is an environmentally widespread process with a number of implications for processes such as sorption and coprecipitation of contaminants and nutrients. Whereas the overall appearance of such aggregates is easily accessible using 2‐D microscopy techniques, the 3‐D and internal structure remain obscure. In this study, we examined the 3‐D structure of cell‐(iron)mineral aggregates formed during Fe(II) oxidation by the nitrate‐reducing Acidovorax sp. strain BoFeN1 using a combination of advanced 3‐D microscopy techniques. We obtained 3‐D structural and chemical information on different cellular encrustation patterns at high spatial resolution (4–200 nm, depending on the method): more specifically, (1) cells free of iron minerals, (2) periplasm filled with iron minerals, (3) spike‐ or platelet‐shaped iron mineral structures, (4) bulky structures on the cell surface, (5) extracellular iron mineral shell structures, (6) cells with iron mineral filled cytoplasm, and (7) agglomerations of extracellular globular structures. In addition to structural information, chemical nanotomography suggests a dominant role of extracellular polymeric substances (EPS) in controlling the formation of cell‐(iron)mineral aggregates. Furthermore, samples in their hydrated state showed cell‐(iron)mineral aggregates in pristine conditions free of preparation (i.e., drying/dehydration) artifacts. All these results were obtained using 3‐D microscopy techniques such as focused ion beam (FIB)/scanning electron microscopy (SEM) tomography, transmission electron microscopy (TEM) tomography, scanning transmission (soft) X‐ray microscopy (STXM) tomography, and confocal laser scanning microscopy (CLSM). It turned out that, due to the various different contrast mechanisms of the individual approaches, and due to the required sample preparation steps, only the combination of these techniques was able to provide a comprehensive understanding of structure and composition of the various Fe‐precipitates and their association with bacterial cells and EPS.